Successful Surgical Abdominal Aortic Debranching Preceding Stent Graft Implantation: A Case Report - Laux, Magdalena L.; Erb, Michael; Hoelschermann, Frank; Albes, Johannes M. (The Thoracic and Cardiovascular Surgeon Reports, 2018)
Background Acute endovascular aneurysm repair with stent grafts (thoracic endovascular aortic repair [TEVAR]) is safe and feasible.Case Description A 64-year-old female presented with a perforated aortic aneurysm of the thoracic descending aorta. Primary TEVAR resulted in good management of the perforation but a type Ib endoleakage remained postoperatively. To place another stent, abdominal debranching with saphenous vein bypass to the celiac trunk was required. In the same session, another endograft was inserted successfully.Conclusion Abdominal debranching is a safe alternative to open aortic repair in acute thoracic and abdominal aneurysms, instead of waiting for a custom-made device.
Keywords: TEVAR; abdominal debranching; celiac trunk; perforated aortic aneurysm